(untitled) (Journal of the College of Basic Education, 2022)
Comparative studies represent an important resource for researchers and academics, providing them with a lot of information about the opinions and doctrines of jurists and their arguments with evidence, and the books of fatwas and studies in them provide multiple possibilities for students in them because of the various jurisprudential opinions they contain that serve Islamic jurisprudence. The research dealt with an important section of Islamic jurisprudence related to inheritance and inheritance and its division in an important book that represents the effort of a great scholar of the Islamic nation. The research was divided into: an introduction, a conclusion, and three chapters: The first: I dealt with the importance of the science of ordinances. The second: I dedicated it to the life of Sheikh Abd al-Karim al-Mudarres (may God have mercy on him) Third: I devoted it to the study of fatwas. It is God’s success